Bioburden proliferation in vehicle air filters waste: the use of gamma radiation on fungal decontamination - SIMONE AQUINO; José Eduardo Alves de Lima; Sueli Ivone Borrely (Brazilian Journal of Radiation Sciences, 2021)
This study aimed to analyze the fungal contamination of air-conditioning filters waste (n=20) as an indicator of Quality Air Indoor from different car models, that were collected from 10 exchange stations located in the South, North, West, Downtown and East, of the city of São Paulo in São Paulo State, Brazil, during the period from October 2017 to November 2018. Sampling of filter particles (33 fragments of 10 × 10-mm size) were plated onto solidified Potato Dextrose agar in Petri dishes. The samples were incubated for 7 days at 25 °C and were stored in a standard Biochemical Oxygen Demand incubator, for growth of fungal cultures. After incubation, the fungal culture in the plates was evaluated, and the total counting of infected fragments was expressed as a percentage. The fungi were examined by Lactophenol blue solution staining for microscopy. All samples were contaminated with various fungal genera, including Aspergillus, Alternaria, Cladosporium, and Penicillium. The study also aimed to evaluate the fungal enumeration in the samples that were irradiated with dose of 10 kGy to fungal decontamination of air-conditioning filters waste. Of total samples, 50% were completed decontaminated, but some genera such as Aspergillus, Penicillium, Rhizopus, Cladosporium and yeasts demonstrated radioresistance at the dose of 10 kGy. The only yeast called Rhodotorula showed an increase in growth after the irradiation process.